2019
DOI: 10.1080/07011784.2018.1503066
|View full text |Cite
|
Sign up to set email alerts
|

A review of simulated climate change impacts on groundwater resources in Eastern Canada

Abstract: In Eastern Canada, groundwater is the main water supply for most of the rural regions and in many large urban communities. An understanding of the impacts of climate change on this resource is crucial for sustainable water management in this region. The objectives of this paper are to summarize the state of knowledge about possible climate change impacts on groundwater dynamics in Eastern Canada thus providing a clearer understanding of future conditions. Twenty-two studies are reviewed including Ontario, Québ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Changes in groundwater dynamics is of critical importance not only for understanding regional water cycles and managing local water resources effectively under changing environment [92], but also for understanding and predicting its ecohydrological consequences [93,94]. A decrease in catchment low flows in the YZRB means a wider range and/or variability of streamflow, which could translate into greater uncertainty for water management [16].…”
Section: Impacts Of Climate Warming On Groundwater Storage Declinementioning
confidence: 99%
See 1 more Smart Citation
“…Changes in groundwater dynamics is of critical importance not only for understanding regional water cycles and managing local water resources effectively under changing environment [92], but also for understanding and predicting its ecohydrological consequences [93,94]. A decrease in catchment low flows in the YZRB means a wider range and/or variability of streamflow, which could translate into greater uncertainty for water management [16].…”
Section: Impacts Of Climate Warming On Groundwater Storage Declinementioning
confidence: 99%
“…In this study, the flow recession method from climatic perspective is demonstrated to be a reliable for understanding the changes in low flow regimes and groundwater storage in a cold mountainous catchment. This method has several advantages, such as requiring only daily Changes in groundwater dynamics is of critical importance not only for understanding regional water cycles and managing local water resources effectively under changing environment [92], but also for understanding and predicting its ecohydrological consequences [93,94]. A decrease in catchment low flows in the YZRB means a wider range and/or variability of streamflow, which could translate into greater uncertainty for water management [16].…”
Section: Impacts Of Climate Warming On Groundwater Storage Declinementioning
confidence: 99%
“…This may be due to the different periods of observation (baseflows, groundwater levels) used as a proxy for GWR or as calibration data for GWR simulations (Rivard et al, 2009), or to the different spatial scales involved. The use of different models can also explain the different results obtained under similar conditions (Larocque et al, 2019;Velázquez et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, GWR has been estimated in various studies in the cold and humid climate of southern Quebec (Canada), but they did not identify obvious trends (Benoit et al, 2014;Chemingui et al, 2015;Croteau et al, 2010;Gagné et al, 2018;Guay et al, 2013;Larocque and Pharand, 2010;Lavigne et al, 2010;Levison et al, 2014Levison et al, , 2016Nastev et al, 2008;Rivard et al, 2009;Rivera, 2014;Saby et al, 2016). This may be due to the relatively short duration of the time series of the variables used as a proxy for GWR (baseflows, groundwater levels; Rivard et al, 2009) and due to the fact that very different models were used in areas of contrasted sizes (Larocque et al, 2019).…”
mentioning
confidence: 99%